Gauss–Newton-based fast and simple recursive algorithm for compensation using shunt active power filter - Chittora, Prakash; Singh, Alka; Singh, Madhusudan (IET generation, transmission & distribution, 2017)
Three-phase, four-wire systems are prone to various power quality (PQ) problems such as load unbalancing, low power factor, harmonics and problem of neutral current. Modified recursive Gauss–Newton (MRGN) algorithm is proposed to mitigate various PQ problems in four-wire distribution systems. The recursive Gauss–Newton method is quite complex, so it is modified to obtain simple and fast MRGN control technique. The proposed algorithm is developed using MATLAB/Simulink environment and tested for mitigation of various PQ problems. Thereafter, a hardware prototype for shunt active power filter (SAPF) is developed along with various sensors, control circuits using dspace 1104 as digital signal processor. Gating circuits provide proper gating pulses to control SAPF as per the new algorithm. Results with linear and non-linear loads have been tested under a variety of loading conditions and thoroughly analysed for its performance.